The Relationship Between Students’ Creativity and Learning Outcomes in Fusion Food Learning at SMKS Aisyiyah Duri - Nur Rahmah Jamil; Wiwik Gusnita; Cici Andriani; Yolanda Intan Sari (Universitas Negeri Padang, 2026)
This study aims to analyze the relationship between students’ creativity and learning outcomes in fusion food learning in class XII of SMKS Aisyiyah Duri. The research method uses a correlational approach. The research sample consisted of 17 students with an r-table value of 0,482, using a saturated sampling technique, where all members of the population were taken as sample. Data was measured using a five-point Likert scale questionnaire and analyzed using normality test (Shapiro-Wilk), linearity tests, Pearson product-moment correlation, and t-tests. The results showed that students’ creativity perception was in the medium to high category, while the learning outcomes of fusion food learning outcomes were in the medium category. The t-test showed a significance value of 0,003 < 0,05, which indicates that there is a relationship between student creativity and learning outcomes. The value of the correlation coefficient r is -0,674 and the value of sig. 0,002 which indicates a strong and significant linear relationship between student creativity and learning outcomes with the direction of negative relationships. It shows that the higher the student’s creativity, the lower the learning outcomes scores tend to be, and vice versa. Therefore, it is necessary to consider teaching strategies and assessments that balance the creative process and competence achievement.